Estimativa do tempo de exposição à radiação solar para desinfecção de águas residuárias domésticas - Queluz, João Gabriel Thomaz [UNESP]; Nicolete, Donizete Aparecido Pastori [UNESP]; Alves, Thaís Regina [UNESP]; Román, Rodrigo Máximo Sánchez [UNESP] (My University, 2015)
The reuse of domestic wastewater in agriculture is an important procedure for the management of water resources. However, these waters contain pathogens which must be previously inactivated. A promising option for the treatment of these waters is solar disinfection. Therefore, the aim of this study was to estimate the time of exposure to solar radiation required for disinfection of domestic wastewater to appropriated levels for agricultural reuse, considering variations of spatial and temporal incidence of solar radiation in the state of São Paulo, Brazil. For this, a mathematical model was used, which represents the remaining population of fecal coliforms in wastewater after its exposure to a certain dose of solar radiation and the solar radiation data were obtained from the SWERA project. From this, 12 maps were generated to represent the efficiency of solar disinfection for all seasons and for three concentrations of total suspended solids in domestic wastewater. The results indicate that the efficiency of solar disinfection varies from season to season. Besides, the best results are obtained in the spring and worse in winter. Moreover, it was observed that the lower the concentration of suspended solids, the greater the potential application of solar disinfection in the state of São Paulo.

O reúso de águas residuárias domésticas na agricultura é uma importante ferramenta para o gerenciamento dos recursos hídricos. No entanto, essas águas contêm patógenos que devem ser previamente inativados. Uma opção promissora para tratamento dessas águas é a desinfecção solar. Portanto, o objetivo deste trabalho foi estimar o tempo de exposição à radiação solar necessário para desinfecção de águas residuárias domésticas até níveis adequados para reutilização agrícola, considerando as variações espaciais e temporais da incidência de radiação solar no estado de São Paulo. Para isso, foi utilizado um modelo matemático que representa a população remanescente de coliformes fecais em águas residuárias após exposição a uma determinada dose de radiação solar e dados de radiação solar obtidos pelo projeto SWERA. A partir disso, foram gerados 12 mapas da eficiência da desinfeção solar, para todas as estações do ano e para três concentrações de sólidos suspensos totais na água residuária doméstica. Os resultados indicaram que a eficiência da desinfecção solar varia de acordo com as estações do ano, sendo que os melhores resultados são obtidos na primavera e os piores no inverno. Além disso, foi observado que quanto menor a concentração de sólidos suspensos, maior o potencial de aplicação da desinfecção solar no estado de São Paulo.
Estimation of solar radiation exposure time required for domestic wastewater disinfection
Keywords: SODIS; Domestic wastewater; Agricultural reuse; SODIS; Águas residuárias domésticas; Reúso agrícola